Phylogenetic analysis among four sections of genus Dendrobium Sw. (Orchidaceae) in Peninsular Malaysia using rbcL sequence data - Moudi, Maryam; Yong, Christina Seok Yien; Salleh @ Japri, Mohd Nazre; Abdullah, Janna Ong; Go, Rusea (Ebioscholar, 2013)
Phylogenetic analysis using chloroplast DNA, the ribulose-bisphosphate carboxylase gene (rbcL), was conducted to examine relationship among four sections of the genus Dendrobium (Orchidaceae): Aporum, Crumenata, Strongyle, and Bolbidium in Peninsular Malaysia. Classifications based on morphological characters have not been able to clearly divide these four sections, therefore deeper and detailed analyses are required to ascertain their status. In this study, the phylogenetic relationships among species of the four sections were investigated to clarify their relations either to lump them into one section or reduce them into two.